“EU MANE GIR HI’ANG” : Model Pengentasan KDRT Dengan Pendekatan Inovasi Berbasis Kearifan Lokal di Provinsi NTT - Maria Fransiska Amu Oyan; Indriyati Indriyati (Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
Violence against women is a complex social problem and remains a significant challenge in Indonesia, including in East Nusa Tenggara Province. The main factors hindering the effective handling of this problem are economic dependence on the perpetrator and the strong culture that views domestic violence as a private matter. This study aims to describe and analyze the implementation of the innovative program "EU MANE GIR HI'ANG" as an alternative approach to alleviating violence against women. The method used is descriptive qualitative with a literature study approach and document analysis. The results show that this model has significant novelty value compared to conventional approaches, by positioning economic recovery as a key element of the solution supported by a local wisdom approach as the program's identity. The program implementation, which includes planning, interventions in the form of capital provision, skills improvement, and structured mentoring, has been proven to have a positive impact on increasing family income, restoring victims' self-confidence, and breaking the chain of economic dependence on the perpetrator. In addition, the use of local cultural identities and values ??increases community acceptance of the program and contributes to reducing negative stigma. Overall, “EU MANE GIR HI’ANG” is an effective intervention model, oriented towards humanitarian values ??and sustainable in encouraging women towards independence and a safe, decent and prosperous life.